Parenting Program to Develop Social and Emotional Ability of Children with Special Needs During the Covid-19 Pandemic - Khairunnisa Ulfadhilah; Erni Munastiwi (Department of Special Education, 2021)
The purpose of this study is to find the right parenting program model for early childhood at RA MH School Cirebon. Management in Parenting is important in nurturing and educating children while at home or outside the home. This research was carried out by RA MH Cirebon. In addition, parenting needs to be applied according to children so that children with special needs will be educated, and parents can stimulate the social skills of children with special needs. This research uses qualitative descriptive research, this research was chosen because it wanted to reveal in more detail and clearly about the management of parenting programs for children with special needs in developing social skills so that they can be a reference for parents and teachers who have students with special needs in educating and providing appropriate stimulation. Because the stimulation given to the crew will be different in stages. This research data collection technique is divided into 3 parts, namely observation, interviews, and documentation. The data analysis technique of this research is divided into 2, namely data reduction and triangulation.